Poor sleep quality among medical students in International Islamic University Malaysia (IIUM) and its association with mental health and other factors - Said, Abdul Hadi; Yusof, Muhammad Zubir; Mohd, Farah Natashah; Azmi, Mohd Addin Nur Hakim; Mohd Hanapiah, Haziqah; Abdullah, Anis Wardati (2020)
INTRODUCTION: Poor sleep quality is a common problem experienced by medical students worldwide. Therefore, this study aimed to measure the prevalence of poor sleep quality among medical students in International Islamic University Malaysia (IIUM) and its association with mental health and other factors. MATERIALS AND METHODS: A cross-sectional study using convenience sampling was conducted among 500 medical students in IIUM Kuantan. A validated self-reported questionnaire including sociodemographic, socioeconomic, lifestyle, Pittsburgh Sleep Quality Index and Depression Anxiety Stress Score 21 was distributed from 15th July to 31st August 2019. Descriptive statistics were used to measure the prevalence of poor sleep quality. Chi- square test, Fisher’s exact test, independent sample T-test, and multiple logistic regression were used to measure the association between risk factors and sleep quality. RESULT: The response rate was 91.2%. The prevalence of poor sleep quality was 59.6%. Multiple logistic regression analysis revealed level of study (clinical year (AOR=0.44, 95% CI: 0.29 - 0.66) and depression (yes (AOR: 1.71, 95% CI 1.03-2.83) contributed independently on poor sleep quality among medical students. There was no significant relationship between tahajjud practice and poor sleep quality. CONCLUSION: More than half of IIUM medical students have poor sleep quality. Those students who were in the pre-clinical year and had depression were independently associated with the occurrence of poor sleep quality. Early intervention is compulsory to overcome this problem among medical students in IIUM.